Identifying and Overcoming Hostility in Mediation of Interpersonal Conflicts - Melnyk, Denys; Hrabovska, Sofiia; Hrebin, Nataliia; Levus, Nadiia (Journal of Education Culture and Society, 2025)
Thesis. The article is devoted to developing practical exercises and recommendations for reducing the level of hostility to avoid serious consequences and find constructive ways of conflict resolution, and developing a conflict mediation plan based on the conflicting parties’ hostility level monitoring. Concept. Organisation of the conflicting parties behaviour monitoring, which makes it possible to recognise hostile attitudes and helps better understand how the conflict affects the interaction between the parties and what emotional reactions and motivations guide their behaviour. Results. The concept of hostility is identified as a stable human characteristic, expressed in the tendency to have a negative attitude towards others, suspicion, aggressiveness and conflict. The psychological aspects of hostility, its impact on emotions, behaviour and perception of the conflicting parties are considered. The effectiveness of methods of establishing markers of hostility, as well as techniques of emotional and behavioural impact on the conflicting parties is analysed. Conclusions. Successful resolution of destructive conflicts is possible only if the attitude between the parties is transformed – from hostile to cooperative. The effectiveness of counseling largely depends on the appropriately chosen format of work: both joint and separate modes of interaction have their strengths and require consideration of the specific circumstances of the conflict. Originality. Practical tools for mediators to reduce the level of hostility between the parties to a conflict are described, including techniques of decentering, word choice, and positive attitudes.